Comparison of the wear particle size distribution of different a-C coatings deposited by vacuum arc - Ren, Ying; Erdmann, Ingo; Khlopyanova, Victoria; Deuerler, Friederike; Buck, Volker (International Conference on Plasma Surface Engineering, 2013)
For biomedical application in the field of artificial hip joints diamond-like carbon (DLC) coatings have been widely studied due to their excellent mechanical, tribological and biological properties. The wear particles as the main factor limiting the life expectancy of hip joints have attracted more and more interest, not only the number of them, but also the distribution of their size. In this study we have deposited DLC coatings on stainless steel (P2000) by a vacuum arc adjustable from anodic to cathodic operation mode. To improve the adhesion of the DLC coating on P2000, titanium as a metallic interlayer was deposited by cathodic vacuum arc evaporation. The frequency distribution of wear particles generated using a disc-on-disc test was measured by a particle size analyzer. It was shown that the maximum of the frequency distribution e.g. at —1000 V bias can be shifted to below 1 µm with increasing anode/cathode diameter ratio da/dc.